Differences Between Subclinical Ruminators and Reflectors in Narrating Autobiographical Memories: Innovative Moments and Autobiographical Reasoning - Habermas, Tilmann; Delarue, Iris; Eiswirth, Pia; Glanz, Sarah; Krämer, Christin; Landertinger, Axel; Krainhöfner, Michelle; Batista, João; Gonçalves, Miguel M. (Frontiers in Psychology, 2021)
Reasoning may help solving problems and understanding personal experiences. Ruminative reasoning, however, is inconclusive, repetitive, and usually regards negative thoughts. We asked how reasoning as manifested in oral autobiographical narratives might differ when it is ruminative versus when it is adaptive by comparing two constructs from the fields of psychotherapy research and narrative research that are potentially beneficial: Innovative Moments and Autobiographical Reasoning. Innovative moments captures statements in that elaborate on changes regarding an earlier personal previous problem of the narrator, and Autobiographical Reasoning capture the connecting of past events with other parts of the narrator’s life or enduring aspects of the narrator. A total of N=94 University students had been selected from 492 students to differ maximally on trait rumination and trait adaptive reflection, and were grouped as ruminators (N=38), reflectors (N=37), and a group with little ruminative and reflective tendencies (‘unconcerned’, N=19). Participants narrated three negative personal experiences (disappointing oneself, harming someone, and being rejected) and two self-related experiences of more mixed valence (turning point and lesson learnt). Reflectors used more innovative moments and more negative than positive autobiographical arguments, but not more overall autobiographical arguments than ruminators. Group differences were not moderated by the valence of memories, and groups did not differ in the positive effect of narrating on mood. Trait depression/anxiety was predicted negatively by innovative moments and positively by autobiographical arguments. Thus, innovative moments are typical for reflectors but not ruminators, whereas the construct of autobiographical reasoning appears to capture reasoning processes irrespective of their ruminative vs. adaptive uses.